Personas and Scenarios as a Methodology for Information Sciences - Singh, Vandana (Qualitative and Quantitative Methods in Libraries, 2019)
This article describes the use of personas and scenarios as a methodology in multiple disciplines and makes a case for the use of this set of methods in information science research. Strengths and weaknesses of personas and scenarios are also discussed to highlight the appropriate use of the methodology.